Efeito de ácidos húmicos provenientes do lodo de esgoto, solo de manguezal e vermicompostos em Zea mays L. - Barcelos, Monique Ellen Farias (2015)
The humic plays an important role in the structure and fertility of the soil. The sludge can be used as a bio fertilizer and contribute to the reduction of costs for farmers with phosphate and nitrogen fertilizers, and increase the accumulation of nutrients in the soil. Humic acid (HA) isolated from vermicompost increase the cation exchange capacity of the soil and the release of nutrients to the plants, promoting plant growth. The aim of this study was to evaluate the physiological, anatomical and biochemical responses of Zea maysL. plants treated or not with HA extracted from sewage sludge, mangrove ecosystem and vermicompost, assessing whether the source of the HA influence on their bioactivity. The results show that significant responses in early growth, photosynthetic pigments content and stomatal density were obtained in plants treated with the concentration of 1 mMC L-1AHLE, and such stimulus was not detected in the hydrolytic activity of the plasma membrane proton pumps (P-H+-ATPase). On the other hand, PPases activity were significantly activated by the treatments